Queering Knowledge Analytics, Devices, and Investments after Marilyn Strathern - Boyce, Paul; Gonzalez-Polledo, E.J; Posocco, Silvia (Theorizing Ethnography, 2020)
This volume draws on the significance of the work of Marilyn Strathern in respect of its potential to queer anthropological analysis and to foster the reimagining of the object of anthropology. The authors examine the ways in which Strathern's varied analytics facilitate the construction of alternative forms of anthropological thinking, and greater understanding of how knowledge practices of queer objects, subjects and relations operate and take effect. Queering Knowledge offers an innovative collection of writing, bringing about queer and anthropological syntheses through Strathern's oeuvre. It will be relevant to scholars from anthropology as well as a number of other disciplines, including gender, sexuality and queer studies. *Winner of the 2020 Ruth Benedict Prize for Outstanding Edited Volume*